1997
DOI: 10.1103/physrevlett.78.2000
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance in the Two-Channel Anderson Lattice

Abstract: The paramagnetic phase of the two channel Anderson Lattice model in the Kondo limit is investigated in infinite spatial dimensions using the non-crossing approximation. The resistivity exhibits a Kondo upturn with decreasing T , followed by a slow decrease to a finite value at T = 0. The decrease reflects lattice coherence effects in concert with particle-hole symmetry breaking. The magneto-resistance obeys an approximate scaling relation, decreasing towards coherent Fermi liquid behavior with increasing field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…Both observations, however, confirm the existence of a characteristic energy scale of a few K in ThAsSe. We note that a negative MR is also expected for a 2CK effect originating from electrical quadrupole moments [30].…”
mentioning
confidence: 94%
“…Both observations, however, confirm the existence of a characteristic energy scale of a few K in ThAsSe. We note that a negative MR is also expected for a 2CK effect originating from electrical quadrupole moments [30].…”
mentioning
confidence: 94%
“…The field dependence we observe is consistent with this view. Finite temperature scaling relations have been reported for the magnetoresistance of UBe 13 [11,16], scaling that is consistent with Kondo physics [7,17]. Unfortunately these scaling arguments do not permit a direct comparison with the field dependence of o (because of the T ¼ 0 extrapolation of the fit) to further our discussion of this parameter.…”
Section: Discussionmentioning
confidence: 57%
“…They are caused by the overcompensated effective impurity on each uranium site acting as an incoherent scatterer. The predicted absence of a Drude peak in the optical conductivity [5] has been found experimentally in UBe 13 [6]. On a lattice, however, the residual entropy [7] is expected to be quenched by a phase transition.…”
Section: Institut F üR Festkörperphysik Technical University Darmstamentioning
confidence: 95%
“…In the TCPAM, the restricted local Hilbert space, consisting of a quadrupolar and a magnetic ground state doublet for two different valence configurations, models a uranium ion in a cubic environment, which can fluctuate between 5f 2 ͞5f 3 or 5f 1 ͞5f 2 ground state configurations. On symmetry grounds, the coupling of the ion to the itinerant electrons via hybridization can be characterized by an orbital and a spin label generating an effective two band model [3].It has been shown that the paramagnetic phase exhibits non-Fermi-liquid properties, as manifest in a large residual resistivity [5]. They are caused by the overcompensated effective impurity on each uranium site acting as an incoherent scatterer.…”
mentioning
confidence: 98%